Implementation Analysis of Electronic Medical Records in Outpatient Services: Insights from 5M Perspective at Nur Hidayah Hospital - Vivi Rahmawati; Wahyu Wijaya Widiyanto (International Forum of Researchers and Lecturers, 2025)
Electronic Medical Records (EMR) are essential for improving the quality, efficiency, and continuity of healthcare services. Despite mandates requiring full implementation of EMRs in Indonesian healthcare facilities by the end of 2023, many hospitals continue to face challenges in achieving effective adoption. This study aims to analyze the implementation of EMRs in the outpatient services of Nur Hidayah Hospital, Yogyakarta, using the 5M framework: Man, Money, Machine, Materials, and Method. Employing a qualitative descriptive approach, data were collected through in-depth interviews, observations, and document analysis involving key informants from medical records staff, registration officers, and IT personnel. The findings revealed that while the availability of staff and supporting infrastructure such as computers and software was generally adequate, limitations persisted in human resource specialization, training access, and system integration. Financial planning for EMR-related needs was done through annual budgeting (RAB), but coordination between departments remained minimal. Key challenges included slow internet connectivity, limited IT staff, and lack of specific Standard Operating Procedures (SOPs) for EMR usage. Overall, the EMR system has been implemented in most outpatient units, yet not all units have fully transitioned due to technical and organizational barriers. This study concludes that optimizing EMR implementation requires not only technological readiness but also organizational alignment, continuous staff development, and robust inter-departmental coordination.